Evaluation of Significance of Liver Enzymes as Screening Tests for the Early Detection of Clinically Asymptomatic Non Alcoholic Fatty Liver Disease in Type 2 Diabetes Mellitus Patients (International Journal of Biomedical and Advance Research, 2015)
Background: Type 2 diabetes mellitus has been linked with abnormal liver function tests. Increased activities of liver enzymes such as aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), ?-glutamyl transferase (GGT) are markers of liver cell injury. Increased activity of these markers is associated with metabolic syndrome, insulin resistance and type 2 diabetes mellitus. This study was aimed to evaluate the significance of liver enzymes such as aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), ?-glutamyl transferase (GGT) in type 2 diabetes mellitus patients. Materials and Methods: Total of 108 cases of type 2 diabetes mellitus patients, comprising of 68 males (62.9%) and 40 females (37%) were included in the study. 110 healthy subjects were includes as controls. Age of the subjects ranged between 27 to 75 years. Serum sample was used for the estimation of study parameters such as FBS, PPBS, AST, ALT, ALP, GGT, Total bilirubin, Direct bilirubin, Total proteins and Albumin. Results: In the present study, mean values of AST, ALT, ALP and GGT were statistically significantly increased in type 2 diabetes mellitus patients when compared to controls (P value 0.001). Conclusion: In this study, we found an association between the increased levels of liver enzymes such as AST, ALT, ALP and GGT in type 2 diabetes mellitus patients. Increased levels of ALT and AST are the surrogate markers for associated non alcoholic fatty liver disease in type 2 diabetes mellitus patients. Hence, testing for AST, ALT, ALP, and GGT should be carried out to screen for underlying non alcoholic fatty liver disease (NAFLD) in type 2 diabetes mellitus patients.